A Novel Method of Making Hinges Using a Newly Designed Sharp Rongeur to Enhance Radiological and Clinical Outcomes in French‐Door Cervical Expansive Laminoplasty. Issue 12 (9th November 2022) - Chen, Ningning; Yu, Lanzhe; Liu, Xizhe; Chen, Guoliang; Li, Yanrun; Zou, Xuenong; He, Dacheng; Yang, Jiaming; Cui, Shangbin; Wang, Le; Liu, Shaoyu; Wei, Fuxin
Abstract : Objective: Although the lamina open angle of making hinges is closely related to the outcomes of French‐door laminoplasty (FDL) for treatment of cervical spondylosis, there have been no methods to predict the lamina open angle preoperatively as yet. The aim of this study was to investigate the accuracy of predicting the laminal open angle using our newly designed sharp rongeur, and to compare the postoperative outcomes and complications between the methods of making hinges using the newly designed sharp rongeur and the traditional high‐speed micro‐drill during the FDL. Methods: This was a single‐center retrospective study. Following the approval of the institutional ethics committee, a total of 39 patients (Male: 28; Female: 11) diagnosed with cervical spondylos who underwent FDL in our institution between January 2018 and May 2019 were enrolled. Patients were divided into two groups based on the method of making hinges (sharp rongeur: 22 cases; high‐speed micro‐drill: 17 cases). The average age at surgery was 59.1 years (range: 16–85 years). The radiological parameters, clinical outcomes, modified Japanese Orthopaedic Association (mJOA) scale score, and the recovery rate of mJOA were recorded and compared between the groups, respectively. The radiological parameters and clinical measurements at pre‐ and post‐operation stages were compared using the paired‐sample t‐ test, the Wilcoxon signed‐rank test, and the Friedman's test, and variables in the two groups were analyzed using an unpaired Student's t ‐test or a Mann–Whitney U test. Results: The average follow‐up period was 20.4 months (range: 14.0–25.9 months), the postoperative open angle was 60.13° ± 3.69° in the rongeur group with 22.78° ± 4.34° of angular enlargement, which was significantly lower than that of 68.96° ± 1.00° in the micro‐drill group with 32.75° ± 4.22° of angular enlargement ( U = 19.000, p < 0.001). The rongeur group showed a higher fusion rate (34.1% vs 14.7%, χ 2 = 11.340, p = 0.001), and a lower fracture rate of the lamina (7.8% vs 25.5%, χ 2 = 14.185, p < 0.001) at 1‐month post‐surgery, compared to the micro‐drill group. There were no significant differences in the clinical outcomes and postoperative complications between the two groups ( p > 0.05), except in the recovery rate of mJOA scores (0.836 ± 0.138 vs 0.724 ± 0.180, U = 115.000, p = 0.042) and neck disability index (NDI) at the final follow‐up (7.55 ± 10.65 vs 14.71 ± 8.72, U = 94.000, p = 0.008). Conclusions: The special sharp rongeur with a tip angle of 20° could be a preferred method to make hinges during FDL, which can predict the laminal open angle accurately and enlarge it to about 23°, thus reducing the fracture rate and accelerating the bony fusion of hinges compared with the outcomes of the traditional micro‐drill method. Abstract : Using the special sharp rongeur is a preferred method to make hinges during French‐door laminoplasty, which can predict the lamina open angle accurately and enlarge it about 23°, reducing the fracture rate and accelerating bony fusion of hinges compared with the traditional micro‐drill method.